Implementasi Simulasi Bencana Oleh Emergensi Respon Tim Di Perusahaan XX Jambi - Pairi, Agus; Ginting, Marinawati; Imran, Suryadi (Jurnal Abdimas Multidisiplin, 2023)
Rescuing victims due to work accidents is the most important thing for companies to be able to guarantee the safety of their employees, there are several cases that occur related to work accidents such as fires that occur at work locations, moreover these companies have a high risk of these incidents, such as oil and gas companies, to It is necessary to carry out education about work safety through a victim rescue simulation carried out by the company's emergency response team. After receiving the training, there is a need for a simulation of the implementation of disaster victim rescue. After carrying out a simulation by the emergency response team of the oil and gas company, the researcher can conclude that it is necessary to make a routine schedule at a minimum every month to carry out a victim rescue simulation by the emergency response team.